Biological screening on the extract of Derris elliptica (TUBA) - Zubairi, Saiful Irwan; Ramli, M. K. A.; Abdul Majid, Fadzilah Adibah; Sarmidi, Mohd. Roji; Abdul Aziz, Ramlan (2005)
Bio-pesticide has an increasing importance in both commercial agriculture and small plot subsistence farming. One of the sources for bio-pesticide is tuba plant, known as Derris elliptica. Rotenone (C23H33O6) is one of the bio-active compounds from Derris elliptica known to be harmless to plants, highly toxic to many insects and relatively innocuous to mammals. From the preliminary results, the optimization study is employed for a Central Composite Design (CCD) using the Design Expert software version 6.0.4 (Stat-Ease. Inc., 2002) is to validate the effects of processing parameters of two selected response variables which are the yield of rotenoids resin and rotenone content respectively. The processing parameter studied is types of solvent (acetone & ethanol), solvent-to-solid ratio (10.0 ml/g & 2.0 ml/g) and raw material particles size (0.5 mm & 5.0 mm). In addition, the biological activity is evaluated for all treatment to obtain the Lethal Concentration (LC50) using brine shrimp, Artemia salina. Various concentrations of rotenone/Concentrated Liquid Crude Extract (CLCE) were exposed in 2 replicates of each concentration for 6, 12 and 24 hours observation respectively. Subsequently, the mortality of the Artemia salina will be evaluated using the probit analysis based on the dose-response curves. The biological activity result shown that the rotenoids resin was considered very active significantly in terms of its toxicity whereby all treatment produced LC50 <_100 ppm after 6, 12 and 24 hours respectively.